Comparison of the respiratory responses to external resistive loading and bronchoconstriction. - Kelsen, S G (1981)
The effects of resistive loads applied at the mouth were compared to the effects of bronchospasm on ventilation, respiratory muscle force (occlusion pressure), and respiratory sensations in 6 normal and 11 asthmatic subjects breathing 100% O2. External resistive loads ranging from 0.65 to 13.33 cm H2O/liter per s were applied during both inspiration and expiration. Bronchospasm was induced by inhalation of aerosolized methacholine. Bronchospasm increased ventilation, inspiratory airflow, respiratory rate, and lowered PACO2. External resistive loading, on the other hand, reduced respiratory rate and inspiratory flow, but left ventilation and PACO2 unaltered. FRC increased to a greater extent with bronchospasm than external flow resistive loads. With both bronchospasm and external loading, occlusion pressure increased in proportion to the rise in resistance to airflow. However, the change in occlusion pressure produced by a given change in resistance and the absolute level of occlusion pressure at comparable levels of airway resistance were greater during bronchospasm than during external loading. These differences in occlusion pressure responses to the two forms of obstruction were not explained by differences in chemical drive or respiratory muscle mechanical advantage. Although the subjects' perception of the effort involved in breathing was heightened during both forms of obstruction to airflow, at any given level of resistance the sense of effort was greater with bronchospasm than external loading. Inputs from mechanoreceptors in the lungs (e.g., irritant receptors) and/or greater stimulation of chest wall mechanoreceptors as a result of increases in lung elastance may explain the differing responses elicited by the two forms of resistive loading.